2014
DOI: 10.1016/j.celrep.2014.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Nontranscriptional Role of Hif-1α in Activation of γ-Secretase and Notch Signaling in Breast Cancer

Abstract: SUMMARY γ-Secretase is composed of four proteins that are obligatory for protease activity: Presenilin, Nicastrin, Aph1 and Pen-2. Despite the progress towards understanding the function of these individual subunits, there is no information available pertaining to the modulation of γ-secretase in response to environmental changes in cells. Here we show that hypoxia upregulates γ-secretase activity through a direct interaction with Hif-1α, revealing an unconventional function for Hif-1α as an enzyme subunit, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 56 publications
2
104
0
8
Order By: Relevance
“…Одним из объектов регуляции HIF-1 является гамма-секретаза: увеличение активности HIF-1 соответствует стимуляции активности этого фермента и опосредованного им Notch-сигнальной трансдукции [19]. При предварительной инкубации микс-культуры нейронов и астроцитов с GSI-I в концентрации 100 нМ, что соответствует эффективной концентрации, не вызывающей значительного снижения жизнеспособности клеток [20], к третьим суткам мы обнаружили статистически значимое увеличение экспрессии TS1, TS2 и, в значительно большей степени, чем при действии ингибитора HIF-1 -MMP-9, на фоне уменьшения экспрессии VEGF (рис.…”
Section: результаты и обсуждениеunclassified
See 2 more Smart Citations
“…Одним из объектов регуляции HIF-1 является гамма-секретаза: увеличение активности HIF-1 соответствует стимуляции активности этого фермента и опосредованного им Notch-сигнальной трансдукции [19]. При предварительной инкубации микс-культуры нейронов и астроцитов с GSI-I в концентрации 100 нМ, что соответствует эффективной концентрации, не вызывающей значительного снижения жизнеспособности клеток [20], к третьим суткам мы обнаружили статистически значимое увеличение экспрессии TS1, TS2 и, в значительно большей степени, чем при действии ингибитора HIF-1 -MMP-9, на фоне уменьшения экспрессии VEGF (рис.…”
Section: результаты и обсуждениеunclassified
“…связь HIF-1 с гамма-секретазой и механизмами сигнального пути Notch [19] позволяет предполагать, что применение FM19G11 и GSI-I имеет однонаправленные эффекты в отношении барьерогенеза in vitro за счёт стимуляции гамма-секретазы и сигнального пути Notch в условиях нормоксии. Ранее было показано, что прямое взаимодействие протеолитически отщеплённого внутриклеточного домена Notch ICD с HIF-1 транскрипционным фактором способствует поддержанию недифференцированного состояния клеток [23].…”
unclassified
See 1 more Smart Citation
“…Recently, Villa et al [163] showed that the master regulator of cellular responses to hypoxia, HYPOXIA-INDUCIBLE FACTOR 1, ALPHA SUBUNIT (HIF1␣), binds directly to ␥-secretase complexes to upregulate ␥-secretase activity under low oxygen. This upregulation did not require increased transcription of ␥-secretase complex components.…”
Section: What Then Of A␤pp A␤ and The A␤ 42 /A␤ 40 Ratio?mentioning
confidence: 99%
“…The recent reports of cryoelectron microscopy structures of intact human γ-secretase have offered novel insights into the function and assembly of this enzyme (21). It is known that only a small portion of the γ-secretase complex is catalytically active (22) and the inactive complex can be activated in response to environmental changes (23).…”
mentioning
confidence: 99%